Healthcare avoidance due to anticipated discrimination among transgender people: A call to create trans-affirmative environments - Luisa Kcomt; Kevin M. Gorey; Betty Jo Barrett; Sean Esteban McCabe (Elsevier, 2020)
Transgender people encounter interpersonal and structural barriers to healthcare access that contribute to their postponement or avoidance of healthcare, which can lead to poor physical and mental health outcomes. Using the 2015 U.S. Transgender Survey, this study examined avoidance of healthcare due to anticipated discrimination among transgender adults aged 25 to 64 (N = 19,157). Multivariable logistic regression analysis was conducted to test whether gender identity/expression, socio-demographic, and transgender-specific factors were associated with healthcare avoidance. Almost one-quarter of the sample (22.8%) avoided healthcare due to anticipated discrimination. Transgender men had increased odds of healthcare avoidance (AOR = 1.32, 95% CI = 1.21-1.45) relative to transgender women. Living in poverty (AOR = 1.52, 95% CI = 1.40-1.65) and visual non-conformity (AOR = 1.48, 95% CI = 1.33-1.66) were significant risk factors. Having health insurance (AOR = 0.87, 95% CI = 0.79-0.96) and disclosure of transgender identity (AOR = 0.77, 95% CI = 0.68-0.87) were protective against healthcare avoidance. A significant interaction of gender identity/expression with health insurance was found; having health insurance moderated the association between gender identity/expression and healthcare avoidance. Providers should consider gender differences, socio-demographic, and transgender-specific factors to improve accessibility of services to transgender communities. A multi-level and multi-faceted approach should be used to create safe, trans-affirmative environments in health systems.